Morphology of congenital portosystemic shunts involving the left colic vein in dogs and cats - White, Robert N.; Parry, A.T. (Wiley, 2016)
OBJECTIVE To describe the anatomy of congenital portosystemic shunts involving the left colic vein in dogs and cats.